Intention Attribution and the Development of Moral Evaluation - Hilton, Brooke C.; Kuhlmeier, Valerie A. (Frontiers in Psychology, 2019)
Research with infants and toddlers suggests that even early in development, humans evaluate others by considering the outcome of an action in relation to the intention underlying it. When someone tries but fails to do a good deed, for example, it seems that it is ‘the thought that counts’. However, research with slightly older children in the preschool years has produced mixed results: in some cases, children are solely considering the positive or negative outcome of an action when evaluating others, while in others, intention attributions are integrated. Such contradictory findings have prompted debate about the development of moral reasoning. Here, we examine extant research on early moral evaluation and propose that differences in the way that task procedures present intention and outcome information can (1) support or preclude young children’s intention attribution and (2) alter the saliency of each kind of information. In turn, these differences would influence the frequency and degree to which young children generate intention-oriented moral evaluations.